Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2010
DOI: 10.1242/jcs.072090
|View full text |Cite
|
Sign up to set email alerts
|

Specific proteolytic cleavage of agrin regulates maturation of the neuromuscular junction

Abstract: SummaryDuring the initial stage of neuromuscular junction (NMJ) formation, nerve-derived agrin cooperates with muscle-autonomous mechanisms in the organization and stabilization of a plaque-like postsynaptic specialization at the site of nerve-muscle contact. Subsequent NMJ maturation to the characteristic pretzel-like appearance requires extensive structural reorganization. We found that the progress of plaque-to-pretzel maturation is regulated by agrin. Excessive cleavage of agrin via transgenic overexpressi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
107
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(113 citation statements)
references
References 29 publications
(57 reference statements)
3
107
0
Order By: Relevance
“…Previous experiments have shown that the z0 splicing isoform is at least 10–20 folds overrepresented over the insert baring splice isoforms (Western blots and internal analyses). The appearance of the z0 splicing variant of the C‐terminal agrin fragments in blood, however, represents the activity of neurotrypsin 42. Further, a vast amount of z0 isoform of agrin is present on the postsynaptic side, which is also cleavable by neurotrypsin.…”
Section: Discussionmentioning
confidence: 99%
“…Previous experiments have shown that the z0 splicing isoform is at least 10–20 folds overrepresented over the insert baring splice isoforms (Western blots and internal analyses). The appearance of the z0 splicing variant of the C‐terminal agrin fragments in blood, however, represents the activity of neurotrypsin 42. Further, a vast amount of z0 isoform of agrin is present on the postsynaptic side, which is also cleavable by neurotrypsin.…”
Section: Discussionmentioning
confidence: 99%
“…CAF is also a peptide fragment cleaved from the nerve-derived protein agrin in neuromuscular remodeling. Normally, the agrin protein is important to maintaining the NMJ [173]. However, excessive cleavage of agrin by the enzyme neurotrypsin leads to functional disintegration at the NMJ [173,174].…”
Section: Circulating Biomarkersmentioning
confidence: 99%
“…Agrin, plays a synaptic coordinator role by easing interpolation of a nerve terminal, clustering of AChRs and maturation of NMJs [5]. This review showcases the task of Agrin in restricting muscular atrophy in SMA by the stabilization of NMJs and thus delaying disease progression, muscle atrophy and also motor impairment.…”
Section: Role Of Agrinmentioning
confidence: 83%